1998
DOI: 10.1002/(sici)1097-4644(19981201)71:3<400::aid-jcb9>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of biotin-containing membranes and nuclear distribution in differentiating human endometrial cells

Abstract: Human Ishikawa endometrial cells form domes when confluent monolayers are stimulated with fresh fetal bovine serum. Extensive structural and biochemical changes have been detected during the approximately 30 h differentiation period. The earliest detectable change involves the formation of multinucleated structures and the appearance of "granules" that stain for biotin within those structures. Nuclei become associated with each other and are ultimately enclosed within a biotin-containing membrane. Aggregated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Walen (2002) The consensus seems to be that endocycling, DNA replication without cytokinesis, is the predominant way in which polyploid cells arise, with syncytial formation recognized as an alternative mechanism. It is syncytial formation that gives rise to polyploid predomes in Ishikawa endometrial cells as previously described (Fleming 1998 andFleming 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Walen (2002) The consensus seems to be that endocycling, DNA replication without cytokinesis, is the predominant way in which polyploid cells arise, with syncytial formation recognized as an alternative mechanism. It is syncytial formation that gives rise to polyploid predomes in Ishikawa endometrial cells as previously described (Fleming 1998 andFleming 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the final stages of detachment the biotin stain is found in the center of polyploid cells in structures that resemble the mitochondrial superstructures (mitonucleons) that envelop nuclear aggregates during dome formation (Fleming et al 1998;Fleming 2016;Fleming 2018). One function of these mitonucleons appears to be the retention of gases (Fleming 2016;Fleming, 2018), and in a single detached cell the retention of gases results in the formation of a unicellular, albeit polyploid, floating spheroid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clones could be isolated that made more and larger domes including a clone that 68 routinely extended domes into everted gland-like structures (Fleming et al, 1998;69 Fleming, 1999;Fleming 2016c As the bubble-like vacuoles enlarge within and compress the heterochromatin, the 143 resulting structure ( fig.3) . 4a).…”
mentioning
confidence: 80%
“…Started from a well-differentiated adenocarcinoma and found to contain estradiol and 48 progesterone receptors (Nishida et al 1985) the cells were shown capable of 49 functions characteristic of normal endometrial cells such as enhanced proliferation in 50 response to estradiol and tamoxifen (Holinka et al,1986a To characterize the process we needed to find conditions that predictably resulted in 57 dome formation (Fleming, 1995), determine what factors enhanced the process 58 (Fleming et al 1998), look for the synthesis of new proteins (Fleming et.al. 1995;59 Fleming 1999), and finally examine the structural changes underlying differentiation.…”
mentioning
confidence: 99%